Clinical characteristics of latent classes of CO2 hypersensitivity in adolescents and young adults. (June 2017) - Rappaport, Lance M.; Sheerin, Christina; Savage, Jeanne E.; Hettema, John M.; Roberson-Nay, Roxann
Abstract: Although breathing CO2 -enriched air reliably increases anxiety, there is debate concerning the nature and specificity of CO2 hypersensitivity to panic risk and panic disorder versus anxiety disorders and related traits broadly, particularly among adolescents and emerging adults. The present study sought to clarify the association of CO2 hypersensitivity with internalizing conditions and symptoms among adolescents and young adults. Participants (N = 628) self-reported anxiety levels every 2 min while breathing air enriched to 7.5% CO2 for 8 min. Growth mixture models were used to examine the structure of anxiety trajectories during the task and the association of each trajectory with dimensional and diagnostic assessments of internalizing disorders. Three distinct trajectories emerged: overall low ( low ), overall high ( high ), and acutely increased anxiety ( acute ). Compared to the low class, the acute class reported elevated neuroticism, anxiety sensitivity, and stress whereas the high class reported elevated anxiety symptoms, depression symptoms, neuroticism, anxiety sensitivity, and increased likelihood of an anxiety disorder diagnosis. Moreover, the acute and high classes reported experiencing a panic-like event at a higher rate than the low class while participants in the high class terminated the task prematurely at a higher rate. The present study clarifies the nature of response to CO2 challenge. Three distinct response profiles emerged, which clarifies the manifestation of CO2 hypersensitivity in anxiety disorders with strong, though not unique, associations with panic-relevant traits. Highlights: Individuals manifest differences in anxiety response to breathing CO2 -enriched air. The classification and meaning of CO2 hypersensitivity is unclear. This study observed that three groups best describe change in anxiety to CO2 air. High and acutely increased anxiety groups had elevated anxiety disorders/traits. CO2 hypersensitivity may be a risk factor for internalizing disorders/traits.